Fluctuations of antimullerian hormone, ovarian follicular reserve, and antioxidant status throughout the estrous cycle in aged mares - Amal M. Aboelmaaty; Abdalla E. A. Elgharieb; Hazem A. El-Debaky; Jamal M. H. Alkhadrawy; Mostafa M. Abou-Ahmed; Abdelraouf M. Ghallab (Open Veterinary Journal)
Background: Senility influences fertility in women and companion animals specially horses.